How Parental Involvement In Activities At School Influences Children’s Learning Outcomes In Mbooni East Sub County, Makueni County, Kenya - Mwania, Judith M.; Koech, Peter Kibet; Amukowa, Wycliffe (Open Access Publishing Group, 2019)
The study sought to underscore the influence of parental involvement in activities at school on learning outcomes among preschool learners. Its purpose was to determine the influence parental involvement in activities at school on learning outcomes among preschool learners in Mbooni Sub County, Makueni County. The study adopted a descriptive survey design that use structured interviews and questionnaire that intended to verify information, perceptions opinions and views of the respondents and an observation schedule for collecting data on the learning outcomes of the children. The dependent variable of the study was learning outcomes among preschool learners in Makueni County, Kenya, while independent variable was parental involvement in activities at school. The target population was teachers, parents and preschool learners in the County. Purposive sampling was used to select the teachers and parents whereas simple random sampling was used to select learners. A sample of 42 teachers, 33 parents and 72 ECDE learners were involved. Validity of the instruments was tested during piloting. Reliability of the instruments was ascertained through testing and retesting to a sample that was not sampled for the actual study. Data was collected after acquiring permit from NACOSTI. Instructions and arrangements on how to collect the data was made with regard to dates agreed between the researcher and the respondents on when to deliver the questionnaire and observe the children during live lessons as well as conducting of the interviews. Data was analyzed using both qualitative and quantitative techniques. Qualitative data was analyzed thematically along the specific themes and presented in narrative forms whereas the quantitative data was analyzed descriptively using frequencies and percentages with the help of Statistical Packages for Social Sciences (SPSS Version 23). The data was presented using tables in order to get the findings. This study may inform teachers, parents and policy makers about the influence of parental involvement in activities at school on children’s learning outcomes in Mbooni East Sub County. The study highlighted the significance of parents- teachers meeting, parent teacher child association, school feeding programmes as well as parents being resource person in passing first-hand information to children as they discuss different roles they undertake in the community. The study thus recommends partnerships of all stakeholders through proper communication and feedback. The National and County Governments should ensure food security in the preschools to enhance school retention, attendance rates, and enrollment for better learning outcomes among other benefits.
Keywords: Parental involvement; Learning outcomes; Preschool learners; Activities and parent teacher association